Accelerated cystogenesis by dietary protein load is dependent on, but not initiated by kidney macrophages - Sedaka, Randee; Huang, Jifeng; Yamaguchi, Shinobu; Lovelady, Caleb; Hsu, Jung-Shan; Shinde, Sejal; Kasztan, Malgorzata; Crossman, David K.; Saigusa, Takamitsu (Frontiers in Medicine, 2023)
Background: Disease severity of autosomal dominant polycystic kidney disease (ADPKD) is influenced by diet. Dietary protein, a recognized cyst-accelerating factor, is catabolized into amino acids (AA) and delivered to the kidney leading to renal hypertrophy. Injury-induced hypertrophic signaling in ADPKD results in increased macrophage (MФ) activation and inflammation followed by cyst growth. We hypothesize that the cystogenesis-prompting effects of HP diet are caused by increased delivery of specific AA to the kidney, ultimately stimulating MФs to promote cyst progression.Methods: Pkd1 flox/flox mice with and without Cre (CAGG-ER) were given tamoxifen to induce global gene deletion (Pkd1KO). Pkd1KO mice were fed either a low (LP; 6%), normal (NP; 18%), or high (HP; 60%) diet for 1 week (early) or 6 weeks (chronic). Mice were then euthanized and tissues were used for histology, immunofluorescence and various biochemical assays. One week fed kidney tissue was cell sorted to isolate tubular epithelial cells for RNA sequencing.Results: Chronic dietary protein load in Pkd1KO mice increased kidney weight, number of kidney infiltrating and resident MФs, chemokines, cytokines and cystic index compared to LP diet fed mice. Accelerated cyst growth induced by chronic HP were attenuated by liposomal clodronate-mediated MФ depletion. Early HP diet fed Pkd1KO mice had larger cystic kidneys compared to NP or LP fed counterparts, but without increases in the number of kidney MФs, cytokines, or markers of tubular injury. RNA sequencing of tubular epithelial cells in HP compared to NP or LP diet group revealed increased expression of sodium-glutamine transporter Snat3, chloride channel Clcnka, and gluconeogenesis marker Pepck1, accompanied by increased excretion of urinary ammonia, a byproduct of glutamine. Early glutamine supplementation in Pkd1KO mice lead to kidney hypertrophy.Chronic dietary protein load-induced renal hypertrophy and accelerated cyst growth in Pkd1KO mice is dependent on both infiltrating and resident MФ recruitment and subsequent inflammatory response. Early cyst expansion by HP diet, however, is relient on increased delivery of glutamine to kidney epithelial cells, driving downstream metabolic changes prior to inflammatory provocation.